Protein expression and gene analyses of HER2, NM23, and K-RAS in gastric cancer and Helicobacter pylori-associated gastritis - Samsudin, Nurulhafizah (2012)
Gastric cancer is ranked as the fourth most common cancer worldwide and the seventh most common cancer in the Malaysian population. Due to its vague and nonspecific symptoms, over 80% of gastric cancer cases were detected in advanced stage, leading to poor survival rate in the patients. Increasing evidence have shown that studies on the molecular biology aspects of Helicobacter pylori-associated chronic gastritis, which is a precursor of gastric cancer, may improve the early diagnosis of gastric cancer. To date, the existing evidence, however, have yet to determine the specific molecular biomarkers that may assist in the diagnosis of early gastric cancer. This preliminary study was done to investigate the role of HER2, nm23 and K-Ras as possible molecular biomarkers in gastric cancer and H. pylori-associated chronic gastritis. A total of 32 cases of gastric cancer and 62 cases of H. pylori-associated chronic gastritis were analyzed using immunohistochemical staining to investigate the protein expressions of HER2, nm23 and K-Ras. Mutational analysis on 15 cases of gastric cancer and 10 cases of H. pyloriassociated chronic gastritis with prominent alterations in protein expressions was performed using polymerase chain reaction and direct sequencing. Our study demonstrated significant increase in the protein expression of nm23 in 62.5% (20/32) of gastric cancer and 33.9% (21/62) H. pylori-associated chronic gastritis and K-Ras in 62.5% (20/32) of gastric cancer and 24.1% (15/62) of H. pylori-associated chronic gastritis using Mann-Whitney U test (P < 0.05). The HER2 was overexpressed in 25.0% (8/32) cases of gastric cancer. However, none of the H. pylori-associated chronic gastritis (0.0%; 0/62) showed HER2 positivity. Using Spearmann’s rank correlation, age was significantly correlated with the nm23 expression in H. pylori-associated chronic gastritis (P = 0.002). Gender was significantly correlated with the K-Ras expression in gastric cancer (P=0.026). For the mutational analysis, no mutation was detected in the HER2 and K-Ras gene. Only one gastric cancer case (6.7%) showed a genetic variation with a C  A transition in the exon 1 of the nm23 gene. In conclusion, our findings suggest that nm23 and K-Ras may play role as possible early biomarkers in gastric cancers and precancerous lesions since significant increase was observed in their protein expressions. However, the absence or low incidence of mutations may indicate that mutations in HER2, nm23 or K-Ras gene have insignificant role in the progression of gastric cancer. Further studies should be performed to further elucidate the role of HER2, nm23 and K-Ras as biomarkers in gastric cancer.